PARADIPLOMASI PROVINSI JAWA TENGAH DALAM MEMPROMOSIKAN UMKM JAWA TENGAH PADA PAMERAN INTERNASIONAL (2019-2023) - Wiyototsani, Muhammad Fadillah; Alam, Gilang Nur; Dermawan, Windy (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the regional economy of Central Java, Indonesia. However, they face resource limitations that impact their performance, especially in foreign trade. To support MSMEs, the Central Java Provincial Government, through agencies like the Industry and Trade Office and the Koperasi and SMEs Office, promotes them via international exhibitions. Notable events from 2019 to 2023 include Festival Indonesia in Moscow, UKM Virtual Expo, a furniture exhibition in Antwerp, and Expo Indonesia en Mexico in Mexico City. The Covid-19 pandemic heightened the need for government intervention to expand MSMEs' markets abroad. This research analyzes these international activities as a form of paradiplomacy, where subnational actors like provincial governments engage in foreign relations. A qualitative research approach was used, involving literature reviews and interviews, with data triangulation to ensure validity and reliability. The findings indicate that the Central Java Provincial Government has successfully promoted MSMEs internationally through paradiplomacy, aligning with national diplomatic strategies and policies aimed at mitigating Covid-19's impact on MSMEs.